Dampak Strategi Problem Based Learning dan Project Based Learning terhadap Hasil Belajar Matematika Ditinjau dari Kreativitas Siswa Sekolah Menegah Pertama - Titik Sudarmi (Manajemen Pendidikan, 2017)
This study aims to test 1) The difference in the effect of learning with Problem BaseLearning and Project Based Learning on learning outcomes in mathematics. 2)Differences in mathematics learning outcomes in terms of the level of creativity ofstudent learning. 3)interaction of approach with the creativity of learners towardsmathematics learning outcomes. The study design Quasi exsperimental. Thepopulation of all eighth grade students of SMP Negeri 1 Kartasura. Sampling withrandom cluster sampling, the sample used is class VIIIH and VIII I. Metode datacollection with documentation, questionnaires, and tests. Mechanical analysis byAnova two way cells are not the same, continued research Scheffe.Hasil method with a significance level of 0.05 indicates: 1) Results of mathematics learning in the class Project Based Learning is 80.21 and the average results of students’ mathematics learning in the class Problem based Learning (PBL) is 69.169. The results of students in the class Project Based Learning is better than the results of student learning in the classroom Problem Based Learning. 2) The ability to think mathematically creativity heavily influence the learning of mathematics. 3) Project Based Learning approach capable of providing better mathematics learning than learning Problem Based Learning approach both for the students creative category, quite creative and less creative.